2010
DOI: 10.1038/ni.1886
|View full text |Cite
|
Sign up to set email alerts
|

An immunoglobulin-like receptor, Allergin-1, inhibits immunoglobulin E–mediated immediate hypersensitivity reactions

Abstract: Anaphylaxis is a life-threatening immediate hypersensitivity reaction triggered by antigen capture by immunoglobulin E (IgE) bound to the high-affinity IgE receptor (FcvarepsilonRI) on mast cells. However, the regulatory mechanism of mast cell activation is not completely understood. Here we identify an immunoglobulin-like receptor, Allergin-1, that contains an immunoreceptor tyrosine-based inhibitory motif (ITIM)-like domain, and show it was preferentially expressed on mast cells. Mouse Allergin-1 recruited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 48 publications
1
71
0
1
Order By: Relevance
“…The ear swelling in Allergin-1-defi cient mice was signifi cantly greater than the ear swelling in WT mice during the entire 50 h observation period after the antigen challenge [ 18 ]. Taken together, these results suggest that Allergin-1 negatively regulates IgE-mediated mast cell activation in vivo and suppresses the type 1 immediate hypersensitivity reactions.…”
Section: In Vivo Analyses Of Allergin-1supporting
confidence: 59%
See 3 more Smart Citations
“…The ear swelling in Allergin-1-defi cient mice was signifi cantly greater than the ear swelling in WT mice during the entire 50 h observation period after the antigen challenge [ 18 ]. Taken together, these results suggest that Allergin-1 negatively regulates IgE-mediated mast cell activation in vivo and suppresses the type 1 immediate hypersensitivity reactions.…”
Section: In Vivo Analyses Of Allergin-1supporting
confidence: 59%
“…Allergin-1-defi cient mice challenged with TNP-OVA showed signifi cantly lower rectal temperatures than the corresponding WT mice (Fig. 4 ) [ 18 ].…”
Section: In Vivo Analyses Of Allergin-1mentioning
confidence: 99%
See 2 more Smart Citations
“…Allergin-1 is studied in the context of allergic responses where it has been shown to suppress IgE-mediated, mast cell-dependent anaphylaxis in mice. In this same study, it has been shown that allergin-1 was expressed on macrophages, neutrophils and dendritic cells as well as mast cells and/or basophils in both humans and mice (36). Interestingly, allergin-1 was also found to be expressed on human B cells (36).…”
Section: Segregation Of Dlbcl Subtypes Based On Glycopeptide Signaturmentioning
confidence: 72%